Handlebody Techniques in Geometric Topology - Bohm, Natalie H. (Tufts Archival Research Center, 2020)
An overview of the use of handle decompositions in the study of manifolds of various dimensions, with particular emphasis put on 3- and 4-manifolds and Kirby calculus. Advisors: Genevieve Walsh and Robert Kropholler.